Effect of tillage and weed management practices on growth, yield attributes and yield of conservation agriculture based wheat (Triticum aestivum L.) - Gaurav Shukla,; R.S. Singh,; Rishabh Singh Chandel,; Sauhard Dubey, (Annals of Agricultural Research, 2023)
A field experiment was conducted during the rabi season of 2017-18 at Acharya Narendra Deva University of Agriculture & Technology, Kumarganj, Ayodhya 224229, (U.P.) to evaluate the effect of various tillage and weed management practices on growth parameters, yield attributes and yield of wheat crop. Results revealed that application of DSR-ZT+R, W-ZT+R, S-ZT (T5 ) resulted in significantly lowest total weed density and total weed dry weight (g/m2 ) at 60, 90 DAS and harvest. The application of Clodinafop + metsulfuron @ 60 + 4 g/ha at 30 DAS fb 1 hand at 45 DAS weeding (W2 ) also registered lowest values of weed density and total weed dry weight at all the growth stages. The application of tillage treatment T5 recorded maximum number of shoots (674.9, 725.8 and 711.1/m2 ) and dry matter accumulation (449.3, 778.8 and 942.2 g) at 60, 90 DAS and harvest, respectively. Among weed management practices, treatment W2 resulted in significantly maximum number of shoots and dry matter accumulation at all the stages of crop growth, except at 30 DAS. The maximum spike length (9.41 cm), grains/spike (46.67), grains weight/spike (1.93 g) and test weight (41.07 g) were recorded with application of tillage treatment T5 . Treatment W2 improved the spike length by 7.36%, grains/spike by 10.14%, grain weight/spike by 11.52 and test weight by 5.06% over control. The mean maximum grain (3881 kg/ha) and straw (5546 kg/ha) yield were recorded with application of tillage treatment T5 . W2 enhanced the mean grain and straw yield of wheat by 7.82% and 7.64%, respectively. The application of tillage treatment T5 and W2 to wheat enhanced the production and productivity.